2009
DOI: 10.3174/ajnr.a1408
|View full text |Cite
|
Sign up to set email alerts
|

CT Angiography Clot Burden Score and Collateral Score: Correlation with Clinical and Radiologic Outcomes in Acute Middle Cerebral Artery Infarct

Abstract: BACKGROUND AND PURPOSE:Clot extent, location, and collateral integrity are important determinants of outcome in acute stroke. We hypothesized that a novel clot burden score (CBS) and collateral score (CS) are important determinants of clinical and radiologic outcomes and serve as useful additional stroke outcome predictors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
524
4
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 622 publications
(557 citation statements)
references
References 43 publications
18
524
4
11
Order By: Relevance
“…1,7,18,25,26 However, very few studies have evaluated both radiologic and clinical factors in the context of CMR. Von Kummer et al 12 showed that a good clinical outcome was more likely in the presence of more distal occlusions, good baseline function, and angiographic recanalization within 24 hours of treatment with IA or IV thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,7,18,25,26 However, very few studies have evaluated both radiologic and clinical factors in the context of CMR. Von Kummer et al 12 showed that a good clinical outcome was more likely in the presence of more distal occlusions, good baseline function, and angiographic recanalization within 24 hours of treatment with IA or IV thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…CBS assigns 10 points to normal ipsilateral vasculature and subtracts points depending on clot location and distribution. 17,18 Two points each are deducted for the supraclinoid ICA segment, proximal MCA, and distal MCA. Infraclinoid ICA, anterior cerebral artery, and the M2 segment of the MCA are each assigned 1 point.…”
Section: Radiologic Parametersmentioning
confidence: 99%
“…As a result, 4D-CTA should also be a stronger predictor of patient outcome after stroke. 51 In a prospective cohort study in 40 subjects, Smit et al 22 compared CTA with TI-CTA calculated from 4D-CTA data in patients presenting with ischemic stroke. Patients with poor collateral circulation on conventional CTA were still found to have good clinical outcome in 31% of cases.…”
Section: Classification Of Arteriovenous Malformations and Arteriovenmentioning
confidence: 99%
“…A 3-grade score (1 = high, 2 = middle, 3 = low) as defined by Knauth et al [20,21] and further refined by CTA post-processing techniques [22] was used as a reference for the evaluation of collaterals. The scale was defined as: (1) contrast filling being visible from pial collaterals to the M1 segment in CTA and DSA, (2) contrast filling being visible from the periphery to M2 branches in CTA and DSA, (3) only peripheral vascular structures show contrast filling.…”
Section: Collateralizationmentioning
confidence: 99%